A comparative study of efficacy and safety of eberconazole versus terbinafine in patients of tinea versicolor - Jyoti Sharma; Jyoti Kaushal; Kamal Aggarwal (Wolters Kluwer Medknow Publications, 2018)
Background: Tinea versicolor (TV) is characterised by the appearance of maculosquamous lesions sometimes associated with mild erythema and pruritus in characteristic areas of the body. Eberconazole and terbinafine though drugs of different classes provide both mycological and clinical cure. Aim: This study aims to compare the efficacy and safety of eberconazole versus terbinafine in patients of TV. Materials and Methods: An open-label, randomised, comparative clinical trial was conducted on 60 patients. The patients were randomly divided into two study groups. Group A: Eberconazole 1% cream once daily and Group B: Terbinafine 1% cream once daily for 2 weeks. Efficacy assessment was done by observing signs and symptoms, i.e., Physician assessment 4-point scale, microscopic KOH examination, Wood's lamp examination, global clinical response assessment, and patient's assessment on visual analog scale at the end of 2 weeks and subsequently patients were reassessed at the end of 4 and 8 weeks to check any relapse. Safety assessment was also done. Results: There was a significant improvement in all the parameters in both groups over a period of 2 weeks. Both the treatment groups, i.e., eberconazole and terbinafine were found to be safe and efficacious at the end of 2 weeks, and no statistically significant difference was observed between the two groups regarding complete cure, i.e., mycological and clinical cure (80% vs. 63.33%), respectively. However, early response (at the end of week 1) was observed with eberconazole. No relapse was seen with eberconazole, but one patient had relapse at 8 weeks with terbinafine. Both drugs had similar safety profile. Conclusion: Although both the drugs cured the disease, eberconazole showed better response as clinical cure and mycological cure were observed earlier and no patient relapsed in the follow-up.